BLOOM'S TACSONOMY FOR THE DISTRIBUTION OF ACADEMIC TIME OF DISCIPLINES FOR THE MILITARY SPECIALISTS PREPARATION - Yurii Y. Repilo; Anatolii V. Halimov; Oleksii M. Shevchenko (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
The approaches to the distribution of budget of time of educational discipline on the basis of analysis of theoretical reasoning of the process of learning and demands to the higher education existing in Ukraine are reviewed in this article. The analysis of state of practical preparation in formation of professional competence of future specialists is done. Main recommendations connected with the enforcing of practical component of teaching are determined.